16S rRNA gene sequencing reveals the relationship between gut microbiota and ovarian development in the swimming crab Portunus trituberculatus. (September 2020) - Wei, Hongling; Li, Xing; Tang, Lei; Yao, Hongzhi; Ren, Zhiming; Wang, Chunlin; Mu, Changkao; Shi, Ce; Wang, Huan
Abstract: Gut microbiota executes many beneficial functions. In this study, the relationship between gut microbiota and ovarian development in the swimming crab P. trituberculatus was explored for the first time. A total of 28 phyla and 422 genera were identified across all samples. However, 105 differential operational taxonomic units, and four differential phyla (Gemmatimonadetes, Actinobacteria, Firmicutes, Marinimicrobia_(SAR406_clade)) were identified. At the genus level, 42 differential genera were identified and 144 bacterial indicators were identified. A key finding was that the relative abundance of 139 indicator bacteria detected in the anisomycin-2 mg/kg group (AK group) was higher than that of blank group (BK group), control group (CK group), SP600125-15 mg/kg group (SK group). In addition, the relative abundance of three indicator bacteria (OTU_236, OTU_1395, OTU_552) detected in the SK group was higher than that of the BK, CK and AK groups. It was also found that the relative abundance of 20 differential genera ( Methyloversatilis, Coprococcus_1, Erysipelotrichaceae_UCG_003, Rikenella, Corynebacterium, Ruminiclostridium, Fusicatenibacter, [Eubacterium]_ruminantium_group, Rikenellaceae_RC9_gut_group, Bifidobacterium, Lachnospiraceae_NK4A136_group, Ruminococcaceae_UCG_014, Christensenellaceae_R_7_group, uncultured_Bacteroidales_bacterium, Coprococcus_2, Desulfovibrio, Aggregatibacter, Ambiguous_taxa, Alloprevotella and Ruminococcaceae_NK4A214_group ) in the SK, BK, CK, and AK group samples were increasing. These differential genera may reveal the relationship between gut microbial communities and ovarian development in P. trituberculatus after injection with the JNK pathway inhibitor SP600125 or the activator anisomycin. In summary, this study provides a new understanding into the relationship between gut microbiota and ovarian development in response to stimulation with inhibitor or activator. Highlights: Gut microbiota in response to stimulation of JNK inhibitor or activator. Most of the discovered 20 differential genera were probiotics. The relationship between gut microbiota and ovarian development in P. trituberculatus.